EXTERNAL BARREL TEMPERATURE OF A SMALL BORE OLYMPIC RIFLE - Bozena Gladyszewska; Piotr Baranowski; Wojciech Mazurek; Joanna Wozniak; Grzegorz Gladyszewski (Termedia Publishing House, 2013)
Investigations on changes in a rifle's barrel temperature during shooting in a rhythm typical for practitioners of Olympic shooting sports are presented. Walther KK300 (cal. 5.6 mm), a typical rifle often used in Olympic competitions, R50 RWS ammunition and a high speed thermographic camera were used in the study. Altair version 5 software was used to process thermal images and a stationary wavelet transform was applied to denoise signals for all the studied points. It was found that the temperature of the rifle barrel does not exceed 0.3°C after one shot whereas the total temperature increase does not exceed 5°C after taking 40 shots and does not affect the position of the hitting point on a target. In fact, contrary to popular belief, the so-called "warming shots" are not done for barrel heating but for cleaning of remnants in the barrel.